Disaster insurance in developing Asia an analysis of market based schemes. - Surminski, Swenja (Economics working papers., 2019)
Well designed insurance schemes can play an important role in increasing resilience to climate and disaster risks. However, the analysis shows that although the use of disaster insurance is expanding, many countries still have no cover available. Where insurance coverage does exist, there is often a reliance on premium subsidies and means to compel uptake, such as mandatory coverage and credit linked products. The paper discusses how this carrot or stick approach affects the sustainability and penetration of climate and disaster risk insurance schemes and efforts to increase resilience.